Efeitos protetores de Lactobacillus delbrueckii UFV-H2b20 na infecção experimental por Listeria monocytogenes em camundongos gnotobióticos - Liliane Martins dos Santos (2007)
Probiotics are formulations containing viable microorganisms that have some beneficial influence on the maintenance of a balanced intestinal microbiota and on the resistance to infections. It has been reported that Lactobacillus delbrueckii UFV-H2b20, a probiotic candidate, is able to protect against infections by stimmulating the hosts immuneresponses. In the present study we investigated the protective effects of L. delbrueckii on the resistance to Listeria monocytogenes infection in gnotobiotic mice. SWISS germfree mice received a single dose containing 109 viable L. delbrueckii. Control mice received salineinstead. Both groups were infected intraperitoneally ten days later with 104 live L. monocytogenes. We showed that L. delbrueckii colonized the gastrointestinal tract of gnotobiotic mice and the number of viable cells ranged 108 to 109 cfu/g of feaces 10 days after monoassociation. Survival data indicated a protective effect of L. delbrueckii against L.monocytogenes infection. Monoassociation induced a faster clearance of L. monocytogenes in the spleen, liver and peritonal cavity 1, 3 and 5 days after infection. Also, production of TNF- in the serum, peritoneal cavity and digestive tract was augmented in monoassociated mice.Levels of IFN- found on supernatants of spleen cells cultures were higher after monoassociation. In addition, increased production of nitric oxide in supernatants of peritoneal cells cultures and in serum was observed in mice that received L. delbrueckii. We also showed that L. delbrueckii was capable of inducing the production of IL-10 in themucosal immune system, but not at the sistemic immune system. In conclusion, it was shown that L. delbrueckii is able to colonize the gastrointestinal tract and enhance host resistance against L. monocytogenes infection through stimulation of inflammatory and regulatory mediators of immune responses.